Nonylphenol and cyproterone acetate effects in the liver and gonads of Lithobates catesbeianus (Anura) tadpoles and juveniles - de Gregorio, Lara Salgueiro [UNESP]; Franco-Belussi, Lilian [UNESP]; Goldberg, Javier; De Oliveira, Classius [UNESP] (Springer Nature, 2021)
Environmental pollution plays an important role in amphibian population decline. Contamination with endocrine disrupting chemicals (EDCs) is particularly worrying due to their capacity to adversely affect organisms at low doses. We hypothesized that exposure to EDCs such as 4-nonylphenol (NP) and cyproterone acetate (CPA) could trigger responses in the liver and gonads, due to toxic and endocrine disrupting effects. Growth rate may also be impaired by contamination. We investigated sublethal effects of a 28-day exposure to three different concentrations of NP and CPA on liver pigmentation, gonadal morphology, body mass, and length of tadpoles and juveniles Lithobates catesbeianus. Liver pigmentation and the gonadal morphologies of treated tadpoles did not differ from control, but growth rate was impaired by both pollutants. Juveniles treated with 10 μg/L NP and 0.025 and 0.25 ng/L CPA displayed increased liver melanin pigmentation, but gonadal morphologies, sex ratios, and body mass were not affected after treatments. The increase in liver pigmentation may be related to defensive, cytoprotective role of melanomacrophages. The decreased growth rate in tadpoles indicates toxic effects of NP and CPA. Thus, contamination with NP and CPA remains a concern and sublethal effects of different dosages of the compounds on native species should be determined.
Keywords: EDCs; Gonads; Growth rate; Liver; Melanin; Pigmentation; Sex ratio